1996
DOI: 10.1128/mcb.16.3.847
|View full text |Cite
|
Sign up to set email alerts
|

Gat1p, a GATA Family Protein Whose Production Is Sensitive to Nitrogen Catabolite Repression, Participates in Transcriptional Activation of Nitrogen-Catabolic Genes in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae cells selectively use nitrogen sources in their environment. Nitrogen catabolite repression (NCR) is the basis of this selectivity. Until recently NCR was thought to be accomplished exclusively through the negative regulation of Gln3p function by Ure2p. The demonstration that NCR-sensitive expression of multiple nitrogen-catabolic genes occurs in a gln3⌬ ure2⌬ dal80::hisG triple mutant indicated that the prevailing view of the nitrogen regulatory circuit was in need of revision; additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
208
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(225 citation statements)
references
References 54 publications
12
208
2
3
Order By: Relevance
“…GAT1 expression was further shown to be autogenously regulated by Gat1 itself. Consistent with the above characteristics, DNA sequencing demonstrated that Gat1 contains a single GATA-binding zinc finger motif common to all well studied members of the GATA family transcription factors, including Gln3, Dal80, and Gzf3 (15,16). NCR-sensitive, GATA factorregulated transcription of GAT1 also correlated with the presence of six cis-acting UAS GATA elements, the core of which was GATAAG, in its promoter (16).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…GAT1 expression was further shown to be autogenously regulated by Gat1 itself. Consistent with the above characteristics, DNA sequencing demonstrated that Gat1 contains a single GATA-binding zinc finger motif common to all well studied members of the GATA family transcription factors, including Gln3, Dal80, and Gzf3 (15,16). NCR-sensitive, GATA factorregulated transcription of GAT1 also correlated with the presence of six cis-acting UAS GATA elements, the core of which was GATAAG, in its promoter (16).…”
mentioning
confidence: 63%
“…However, detailed genetic analyses using single, double, and triple gln3, dal80 (a GATA family repressor), and ure2 mutants led to the demonstration that NCR-sensitive transcription could be activated not only by Gln3, but also by another unknown transcription factor whose production and operation were themselves NCR-sensitive, Gln3-dependent, and Dal80-and Ure2-regulated (11)(12)(13)(14). The transcription factor whose existence was predicted in that early work was subsequently cloned and designated GAT1/NIL1 (15,16). Analysis of GAT1 transcription was then investigated using Northern blot and lacZ reporter-gene fusions (16 -21).…”
mentioning
confidence: 99%
“…This pathway ensures that genes encoding proteins required for the usage of poor nitrogen sources are repressed when rich nitrogen sources, such as glutamine, are present in sufficient quantities. Four GATA family zinc-finger transcription factors are involved in the transcriptional control exerted by the NDP: two activators, Gln3 and Gat1, and two repressors, Dal80 and Gzf3 (Minehart and Magasanik 1991;Coffman et al 1995Coffman et al , 1996Coffman et al , 1997Cooper 2002). TORC1 inhibits transcription of NDP genes by controlling Gln3 and Gat1 function (Beck et al 1999;Cardenas et al 1999;Hardwick et al 1999;Shamji et al 2000).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…By this reasoning, Dal82p might not contain a transcriptional activation motif (53). Therefore, we transformed WT EGY48 cells with lexAlacZ transcriptional activation reporter pSH18-34, pSH18-34 ϩ vector pBTM116 (45,46), or pSH18-34 ϩ lexA-DAL82 pSS82BTM (15,16). High level activation occurred only in lexA-DAL82 pSS82BTM transformants (Fig.…”
Section: Dna-binding Domain Of Dal82p-dal82pmentioning
confidence: 99%